Model for Determining Sustainable Food Agricultural Land through a Spatial Optimization Approach in Bantul Regency - Budiyanto Budiyanto; Cahyono Susetyo; Muhammad Daffa Musyary; Annisya Alifvia Soehartono (Faculty of Engineering, Andi Djemma University, 2024)
Land use is a characteristic of the arrangements, activities, and contributions made by humans to either effect changes or maintain a certain type of land cover (Gregorio and Jansen, 1998). Agricultural land is a crucial resource for sustainability and food security. In an effort to control and anticipate the conversion of agricultural land, the Bantul Regency Government has issued Regional Regulation No. 10 of 2023 on the Protection of Sustainable Food Agricultural Land, with a total area of 12,831 hectares. However, the area designated for protection according to the 2021 study recommendations is 14,407.50 hectares. This represents a reduction of 1,576 hectares due to agricultural land in Sewon and Kasihan Districts being planned for non-agricultural use. Therefore, the objective of this study is to identify the modeling of sustainable food agricultural land designation in Bantul Regency, using a linear programming optimization approach with the aid of Microsoft Excel Solver. The linear programming model, with the objective function to minimize the area designated in the regional regulation, determined the need for 11,356.52 hectares of agricultural land to maintain food security in Bantul Regency over a period of 20 years.